Vaccine Efficacy and Safety in Patients with Celiac Disease - Rocco Scarmozzino; Giovanna Zanoni; Alessandra Arcolaci; Rachele Ciccocioppo (Vaccines)
Celiac disease (CD) is an autoimmune disorder caused by gluten intake in genetically predisposed individuals. This article provides an overview of the available data on the risks of infectious diseases and the mechanisms involved in CD, including a detailed analysis of vaccine efficacy, immunogenicity, and safety. The published articles were retrieved from the PubMed database using the terms “celiac disease”, “efficacy”, “hyposplenism”, “immune response”, “infections”, “immunization”, “immunogenicity”, “safety”, “vaccination”, and “vaccine”. CD can be associated with several autoimmune diseases, including selective immunoglobulin A deficiency (SIgAD), altered mucosal permeability, and hyposplenism. These conditions entail an increased risk of infections, which can be prevented by targeted vaccinations, although specific recommendations on immunization practices for subjects with CD have not been released. Regarding vaccinations, the immune response to the Hepatitis B virus (HBV) vaccine can be impaired in patients with CD; therefore, proposed strategies to elicit and maintain protective specific antibody titers are summarized. For patients with conditions that put them at risk of infections, vaccinations against Pneumococcus and other encapsulated bacteria should be recommended. Based on the available evidence, the Rotavirus vaccine offered to children could be useful in preventing CD in at-risk subjects. Overall, except for the HBV vaccine, vaccine efficacy in patients with CD is comparable to that in the general population, and no safety concerns have arisen.